PLACE BRANDING APPROACH AS AN EFFORT TO OPTIMIZE THE IMAGE OF THE REGENCY OF BELITUNG AND THEIR IMPLICATIONS FOR THE DECISION TO VISIT TOURISM DESTINATIONS IN LENGKUAS ISLAND - C Christianingrum; Nizwan Zukhri; Nur Ahmad Ricky Rudianto (Integrated Journal of Business and Economics (IJBE), 2022)
This study aims to find out about the Place branding approach to optimize the image of Belitung Regency and its implications for the decision to visit tourist destinations on the Lengkuas Island. The object of this research is the tourists who visit the tourist destinations of the Belitung Regency. The research method uses descriptive and verification. Sources of data used are primary and secondary. The research sample was 100 people, using the Proportional Sampling technique. Data collection techniques are carried out through questionnaires, interviews, and literature studies. To measure the value of the Place branding approach to optimize the image of the Belitung Regency and its implications for the decision to visit the tourist destination of Lengkuas Island.